2016 24th European Signal Processing Conference (EUSIPCO) 2016
DOI: 10.1109/eusipco.2016.7760319
|View full text |Cite
|
Sign up to set email alerts
|

Multiple source localization in the spherical harmonic domain using augmented intensity vectors based on grid search

Abstract: Multiple source localization is an important task in acoustic signal processing with applications including dereverberation, source separation, source tracking and environment mapping. When using spherical microphone arrays, it has been previously shown that Pseudo-intensity Vectors (PIV), and Augmented Intensity Vectors (AIV), are an effective approach for direction of arrival estimation of a sound source. In this paper, we evaluate AIV-based localization in acoustic scenarios involving multiple sound sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…In [38] and [23], we have shown that the conventional wideband PWD-SRP fails in localization of multiple sources especially for adjacent sources as the summation of power spectra can result in merging of adjacent peaks associated to different sources resulting in an erroneous estimated DOA between the sources as seen in Fig. 1.…”
Section: B Pwd-srp In Shdmentioning
confidence: 99%
See 2 more Smart Citations
“…In [38] and [23], we have shown that the conventional wideband PWD-SRP fails in localization of multiple sources especially for adjacent sources as the summation of power spectra can result in merging of adjacent peaks associated to different sources resulting in an erroneous estimated DOA between the sources as seen in Fig. 1.…”
Section: B Pwd-srp In Shdmentioning
confidence: 99%
“…In [38], [23] we proposed Augmented Intensity Vectors (AIVs) which exploits eigenbeams of order ≥ 2 to form vectors with improved DOA accuracy compared to PIVs. These vectors are obtained using spatially constrained grid search to minimize a cost function with initialisation derived from PIVs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The MUSIC spectrum in (11) and (18) was calculated with 1°resolution across azimuth and inclination (360 × 181). Incoherent DPD-MUSIC was excluded from our evaluation since studies in [13] show that incoherent DPD-MUSIC fails in case of low angular separation of sources as the two peaks associated with two adjacent sources can be merged into one peak over summation of MUSIC spectra which causes the second highest peak to be detected far from the sources.…”
Section: Evaluationsmentioning
confidence: 99%
“…The initial DOA estimates (one per TF bin) can be obtained by any SS DOA estimator such as PIV [10], as used in this work, Augmented Intensity Vectors (AIVs) [12], [13], Steered Response Power-based methods [14] or SS MUSIC. The initial DOA estimates are weighted based on their consistency within a time interval and the ones with the strongest weights are selected as the most consistent DOAs using the assumption of stationary sources.…”
Section: A Msecmentioning
confidence: 99%